Subglottic Stenosis After Double‐Lumen Tube Intubation With Reintubation: A Case Report and Review of Japanese Cases - Masami Suzuki; Naohiro Yoshida (Clinical Case Reports)
ABSTRACT Subglottic stenosis after double‐lumen tube (DLT) intubation is more likely to occur when an oversized DLT, specifically a 35 Fr DLT, is used in older, shorter women. Reintubation in such cases is challenging and may cause additional traumatic laryngitis. Tracheostomy is the best management for subglottic stenosis after DLT intubation.